HUBUNGAN PAPARAN MEDIA INTERNET DENGAN PERILAKU SEKS BEBAS PADA REMAJA DI SMA NEGERI I PERCUT SEI TUAN TAHUN 2015 - Irka Setiawati (Jurnal Ilmiah Kebidanan Imelda, 2016)
The main problems among the teenagers are sexual problem or TRIAS KLASIK (sex before marriagge unexpected pregnancy, abortion), sexual contagious infection, HIV and AIDS and drugs abused.the free information from internet like facebook, twitter, youtobe and others can provide them pornography. In the survey in 2013 in United States, the women were more often used social media than men. The researches in USA, England, and Australia showed that in 2009, 40-50% teenagers around 13 - 17 had ever had sex, 80% boys and 70% girls are sexually active and the first time they did it was at the age of 16. This study is aimed to see the relation between social media exposure and free sex in SMA Negeri I Percut Sei Tuan. The Population were all students in SMA Negeri 1 Percut Sei Tua, and the samples were 114 students. The samples were taken by Simple Random Sampling. The result of the study from the Chi square test shows that frequency, duration, porn site and social media access relate with free sex behavior with P value < 0,05. The result of multivariate test with logistic regression show that there is relation between internet exposure and free sex behavior. The most dominant is the duration with p value 0,000 < 0,05. The biggest score Exp B is 45,949. Thus it can be concluded that the hipothesis is accepted. It is suggested to the school to give more counselling about free sex. It should be given continuosly to prevent them from doing free sex.